FACTORS AFFECTING HEMOGLOBIN LEVEL AMONG HIV POSITIVE PATIENTS TAKING HIGHLY ACTIVE RETROVIRAL THERAPY - Durga Devi1 , Ikram Din Ujjan2 , Kiran Aamir3 , Osheen Vandana Shahani4 , Laraib Memon5 , Ashok Kumar Lohana6 . (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT INTRODUCTION: Infection with the Human Immunodeficiency Virus (HIV) is a global public health issue. At the beginning of this century, Pakistan transitioned from a low prevalence to a high risk and subsequently to a concentrated pandemic. Among the many adverse effects of the illness, is a marked disturbance in the hematological indices, chief among which is the level of hemoglobin (Hb). In addition to the disease, other factors too may be responsible for catalyzing this change. OBJECTIVE: To determine factors affecting Hb level among HIV infected patients. METHODOLGY: In this cross-sectional investigation, 254 HIV patients of either gender who were at least 18 years old were included in the sample. After obtaining written informed consent, information was entered onto a structured questionnaire that included questions about fundamental bio data, socio-demographic information, medical history, conclusions drawn from a general physical and systemic examination, and a baseline hematological examination. With the help of MS Excel 365 and SPSS version 21.0, the data was examined. RESULTS: The sample’s median age was 34 years old (SD: 5). The majority of the sample was made up of middle-aged males from rural backgrounds with a middle socioeconomic position. Anemia was present in 85.8% of the sample overall, with the majority of those affected experiencing mild to moderate anemia and only a small number dealing with severe anemia. CONCLUSION: After careful consideration, genders, age, socioeconomic status and duration of illness were recognized as factors affecting the Hb level among HIV infected patients.